Clinical performance of posterior inlay-retained and wing-retained monolithic zirconia resin-bonded fixed partial dentures: Stage One Results of a Randomized Controlled Trial - Bömicke, Wolfgang; Rathmann, Friederike; Pilz, Maximilian; Lorenzo Bermejo, Justo; Waldecker, Moritz; Ohlmann, Brigitte; Rammelsberg, Peter; Zenthöfer, Andreas (Journal of prosthodontics, 2021)
Purpose To prospectively compare the clinical performance of posterior inlay-retained and wing-retained monolithic zirconia fixed partial dentures (FPDs). Materials and methods After simple randomization, 30 participants received either one inlay-retained (n = 15; mean age: 56.38 ± 12.70 years; 10 men [66.7%]) or one wing-retained (n = 15; mean age: 45.90 ±13.24 years; 7 men [46.7%]) FPD. The restorations, which predominantly replaced first molars, were fabricated from translucent, 3 mol% yttria-stabilized zirconia and attached with self-etching resin cement. Restorations and abutment teeth were clinically followed up for complications one week and 3, 6, and 12 months after cementation. Plaque and gingival scores, probing pocket depths, and attachment levels were recorded for the abutment and contralateral reference teeth both before treatment and during follow-up examinations. The restorations were also assessed in accordance with FDI World Dental Federation criteria. Statistical analyses were conducted with R (α = 0.05). An adaptive, 2-stage study design based on the incidence of failure-free survival in the groups after 12 months (stage 1) was implemented. Predefined decision rules were used to determine whether further recruitment (stage 2) would enable the detection of a statistically significant difference between the restoration designs with sufficient power. Results During 12 months, only one wing retainer debonded which required removal of the FPD. Failure-free survival was thus 93.3% for wing-retained and 100% for inlay-retained FPDs (log-rank test, p = 0.317). Moderate aftercare resulted in intervention-free rates of 78.8% and 86.7% for inlay-retained and wing-retained restorations, respectively (log-rank test, p = 0.605). Based on FDI World Dental Federation criteria, all restorations were acceptable at the 12-month follow-up (Fisher-Boschloo test, p = 0.161). Plaque, gingival, and periodontal scores remained practically unchanged from before treatment to the 12-month follow-up. Recruitment was stopped after stage 1 because, based on the small difference in the incidence of failure-free survival in the groups, it was accepted that it would not be possible to recruit the necessary number of participants to show a statistically significant difference between the retainer designs. Conclusions Both inlay-retained and wing-retained monolithic zirconia resin-bonded FPDs performed well for the 12-month, short-term follow-up period.
First published: 13 September 2020
Gesehen am 25.10.2021